Management Umrah Handling Services at Soekarno Hatta Airport (Study Case in CV. Titian Jaya) - MD Sukamto; Asep Sugara; Yadi Haholongan Mendrop (Fakultas Bisnis, 2023)
This type of research is field research conducted at CV. Titian Jaya at Soekarno-Hatta International Airport. Researchers took samples using a purposive sample, namely taking subjects based on predetermined traits or characteristics, so the sample from this study amounted to 6 people as research key informants. The results of this study indicate that the management of Umrah handling services at CV. Titian Jaya, the company's plan is to re-check all requirements and cooperation with related clients. Organizing in this company is grouping or interrelated between divisions with other divisions. The movement carried out in this case is to do all the work according to their respective duties. Supervision carried out is supervising the entire series of activities whether they are in accordance with what has been agreed or not. Services provided by CV. Titian Jaya covers administration, transportation, accommodation, consumption, and health. Suggestions for the results of the research are the implementation of supervision and evaluation of programs that are currently running or those that are already running. With the aim of making Umrah pilgrimage services even better in the future